Sistem Pendukung Keputusan Kenaikan Jabatan Karyawan Menggunakan Kombinasi Metode SMART-TOPSIS - Dandi Permadi; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Promotion of employees at the Center for Quality Testing for Veterinary Medicine Certification (BBPMSOH) is still done manually, so it is possible that decisions are made subjectively by only looking at certain aspects, in selecting employees who only look at their daily habits while working. is not effective. Seeing the existing problems, it is necessary to SPK that can help solve problems in decision making by adjusting the criteria and weights that have been determined by the company. The method used in decision making is the SMART-TOPSIS method, with this method we can find out which employees are included in the weights and criteria for promotion at the (BBPMSOH). The existence of problems at the (BBPMSOH) requires a Decision Support System in determining employee promotions. system development using systematic and sequential software that will be built using the PHP programming language, and the MySQL database. The final result in this study is the establishment of a Decision Support System for Employee Promotion at the (BBPMSOH) With the SMART-TOPSIS method based on this website, it can determine employees who are worthy of consideration and have not been selected to choose one of the best in occupying the position. office position. After the decisions obtained in the decision support system application, the system will display the results of the decisions that have been taken.